2023
DOI: 10.3390/ijms241914994
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA as Possible Mediators of the Synergistic Effect of Celecoxib and Glucosamine Sulfate in Human Osteoarthritic Chondrocyte Exposed to IL-1β

Sara Cheleschi,
Nicola Veronese,
Serafino Carta
et al.

Abstract: This study investigated the role of a pattern of microRNA (miRNA) as possible mediators of celecoxib and prescription-grade glucosamine sulfate (GS) effects in human osteoarthritis (OA) chondrocytes. Chondrocytes were treated with celecoxib (1.85 µM) and GS (9 µM), alone or in combination, for 24 h, with or without interleukin (IL)-1β (10 ng/mL). Cell viability was determined using the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay, apoptosis and reactive oxygen species (ROS) by cytom… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 88 publications
0
1
0
Order By: Relevance
“…Results from an in vitro study on human osteoarthritic chondrocytes showed that a combination of celecoxib and glucosamine sulfate exert synergistic anti-inflammatory and chondroprotective effects on osteoarthritic chondrocyte metabolism, apoptosis, and oxidative stress through the modulation of the NF-κB pathway. 26 So it is necessary to investigate whether imrecoxib has similar synergistic effects in vitro and in patients with osteoarthritis.…”
Section: Methodsmentioning
confidence: 99%
“…Results from an in vitro study on human osteoarthritic chondrocytes showed that a combination of celecoxib and glucosamine sulfate exert synergistic anti-inflammatory and chondroprotective effects on osteoarthritic chondrocyte metabolism, apoptosis, and oxidative stress through the modulation of the NF-κB pathway. 26 So it is necessary to investigate whether imrecoxib has similar synergistic effects in vitro and in patients with osteoarthritis.…”
Section: Methodsmentioning
confidence: 99%